2010
DOI: 10.1111/j.1460-2695.2010.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of fatigue crack propagation in ductile metallic materials

Abstract: A B S T R A C T An overview of our research performed during the last 15 years is presented to improve the understanding of fatigue crack propagation mechanisms. The focus is devoted to ductile metals and the material separation process at low and intermedial crack propagation rates. The effect of environment, short cracks, small-scale yielding as well as large-scale yielding are considered. It will be shown that the dominant intrinsic propagation mechanism in ductile metallic materials is the formation of new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 50 publications
3
55
0
Order By: Relevance
“…Despite this difference the relation between CTOD and da/dN is not affected. On the contrary, in the standard da/dN versus K diagram the difference between the long and short crack data is huge (see [17]). The grain size of the austenitic steel A220, used for the short crack experiments in Figs.…”
Section: Do Short Fatigue Cracks Propagate By a Different Mechanism?mentioning
confidence: 99%
See 3 more Smart Citations
“…Despite this difference the relation between CTOD and da/dN is not affected. On the contrary, in the standard da/dN versus K diagram the difference between the long and short crack data is huge (see [17]). The grain size of the austenitic steel A220, used for the short crack experiments in Figs.…”
Section: Do Short Fatigue Cracks Propagate By a Different Mechanism?mentioning
confidence: 99%
“…4 the measured CTOD are plotted as a function of the crack growth rate. The data obtained from [17], where the samples had a crack length of about 30 mm are also indicated. It is evident that the crack propagation rate is about one-fourth of CTOD independent of the crack length or notch depth.…”
Section: Do Short Fatigue Cracks Propagate By a Different Mechanism?mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it was also reported that the presence or absence of oxygen and water vapor cause a significant change of fatigue striation morphology on the fracture surface [30]. In general, the fatigue striations in non-aggressive environments are formed through the repetition of normal slip-off in loading processes and reverse-slip during unloading processes [32]. McEvily et al found that the striations of Type304 stainless steel in a vacuum environment become more blurred in appearance compared to those formed in air, and discussed these differences with reference to the crack blunting process [30].…”
Section: Comparison Of the Tg Fracture Morphology Formed In Air Nitrmentioning
confidence: 99%